Landmarks in organo-transition metal chemistry : a personal view - Werner, Helmut (Springer, 2017)
"This book is a little treasure. It will become indispensable reading for those interested in organometallic chemistry and the profound impact that this area of research has had in the chemical sciences and the chemical industry. In an extraordinarily well-documented manner, the book presents the historical development of organometallic chemistry from the early 19th century until the present. It is written in an elegant, readable style and at the same time with great scientific rigor. The historical notes that pervade every chapter are very effective at capturing the attention of the reader and will be especially useful for students, who should be exposed to this side of chemistry. Both researchers and university teachers alike will find Landmarks in Organo-Transition Metal Chemistry: A Personal View a very useful companion." -Ernesto Carmona, Instituto de Investigaciones Quimicas, University of Seville "Professor Werner has produced a scholarly volume full of fascinating facts and insights into many of the key developments and episodes in the growth of our knowledge of organometallic chemistry. Stories of the development of experimental and theoretical topics are presented and interwoven with an insight attributable to the extensive personal knowledge and experiences of the author. I recommend this book as a valuable contribution to scholarship and as a jolly good read." -Malcolm L.H. Green, FRS, Department of Chemistry, Oxford University